1989
DOI: 10.1105/tpc.1.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of leaf development in C4 plants.

Abstract: REVIEW INTRODUCTIONThe differentiation of cell types in plants depends on the continuous interpretation of positional information. Plant organs are established by patterns of cell division that are often highly variable, yet the final arrangement of cell types within each organ remains the same. A current challenge is to understand the means by which cells of varying clonal history arrive at the same differentiated fate in the development of a plant organ. The ideal system for the study of this developmental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(20 citation statements)
references
References 60 publications
(85 reference statements)
0
20
0
Order By: Relevance
“…While no bundle-sheath protoplasts were released from maize and Sorghum strands under these conditions -even after digestion for up to 12 h and similar treatment only low yields of bundle-sheath protoplasts were obtained (cf. [27] the procedure rendered the bundle-sheath cells susceptible to breakage by gentle mechanical treatment. After digestion, the bundle-sheath strands were collected in a commercially available tea strainer and then transferred onto a 80 /2m mesh that was submersed in 200 ml of blending medium II.…”
Section: Isolation Of Intact Mesophyll and Bundle-sheath Chloroplastsmentioning
confidence: 99%
See 1 more Smart Citation
“…While no bundle-sheath protoplasts were released from maize and Sorghum strands under these conditions -even after digestion for up to 12 h and similar treatment only low yields of bundle-sheath protoplasts were obtained (cf. [27] the procedure rendered the bundle-sheath cells susceptible to breakage by gentle mechanical treatment. After digestion, the bundle-sheath strands were collected in a commercially available tea strainer and then transferred onto a 80 /2m mesh that was submersed in 200 ml of blending medium II.…”
Section: Isolation Of Intact Mesophyll and Bundle-sheath Chloroplastsmentioning
confidence: 99%
“…As first steps towards an understanding of the mechanisms controlling the C4-specific expression of plastid genes, protein and mRNA levels were investigated using northern and western analysis (reviewed in [27]). For rbcL and the plastome-located photosystem II genes, it has been shown that the differences in the protein levels found in mesophyll and bundle-sheath chloroplasts correlate with differences in the levels of the corresponding transcripts, which implicates that the C4-specific expression of plastid genes is regulated at the level of mRNA abundance [21,29,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…nitrogen assimilation, biosynthesis of lipids) necessitates the preference for a linear photosynthetic electron transport in thylakoid membranes of these cells, and thus for a high amount and photochemical activity of PS2, associated with high granality of MC chloroplasts' thylakoids (Chow et al 2005, Majeran et al 2005. On the other hand, the biosynthesis and the accumulation of starch take place preferentially (but not exclusively) in the BSCs, which are often filled up with starch inclusions (Spilatro and Preiss 1987, Nelson and Langdale 1989, Lunn and Hatch 1995, Majeran et al 2005.…”
Section: Introductionmentioning
confidence: 97%
“…the bundle sheath cells (BSCs) surrounding the vascular bundles, and the mesophyll cells (MCs), which in turn surround the BSCs. The arrangement of these cells in leaves of NADP-ME plants follows the pattern referred to as the Kranz anatomy (Kranz is the German word for "wreath"), where the two cell layers give the appearance of wreath surrounding each vein (Furbank and Foyer 1988, Nelson and Langdale 1989, Nelson and Dengler 1992, Edwards et al 2001, Leegood 2002, Brown et al 2005. The BSCs and MCs differ in their structural properties; the most conspicuous feature of BSCs being their larger size compared to MCs, their thick cell walls, and the centrifugal or centripetal ---(NAD-malate type) arrangement of chloroplasts (Nelson and Langdale 1989, Dengler et al 1994, Leegood 2002, Brown et al 2005.…”
Section: Introductionmentioning
confidence: 98%
“…Plants utilizing the C4 pathway of photosynthesis possess a specialized leaf anatomy quite different from the loose arrangement of parenchyma (spongy and palisade mesophyll cells) typical of C3 plants (for review see [24]) C 4 'Kranz' anatomy comprises two major photosynthetically active cell types centrifugally arranged about the vascular bundles. These two cell types cooperate in a multi-step scheme of CO2 fixation, the C4 pathway.…”
Section: Introductionmentioning
confidence: 99%